Swallowing and communication outcomes following primary transoral robotic surgery. Issue 7 (9th March 2021) - Charters, Emma; Wu, Raymond; Milross, Chris; Bogaardt, Hans; Freeman‐Sanderson, Amy; Ballard, Kirrie; Davies, Sarah; Oates, Justine; Clark, Jonathan
Abstract: Background: Heterogeneity within studies examining transoral robotic surgery (TORS) for oropharyngeal cancer (OPC) has made it challenging to make clear conclusions on functional outcomes. Infrequent use of instrumental swallow examinations compounds uncertainty surrounding the proposed functional advantage to TORS. Methods: A prospective cohort of 49 patients underwent speech and swallowing assessment 12 months following treatment for OPC. Patients were assessed using fibreoptic endoscopic evaluation of swallowing (FEES), clinician‐ and patient‐reported outcomes. Participants were matched according to tumor site, T category, and age. Speech and swallowing outcomes were compared for those receiving TORS versus chemoradiation. Results: When adjuvant radiotherapy to the primary site could be avoided, TORS demonstrated an advantage for feeding tube duration, secretion severity, penetration/aspiration, M. D. Anderson Dysphagia Inventory (MDADI), and airway protection. Conclusion: This explorative study suggests that a treatment philosophy of selecting patients for TORS where adjuvant therapy can be omitted or confined to the neck warrants further evaluation.